Investigation of Campylobacter concisus gastric epithelial pathogenicity using AGS cells - Luk, Christopher Yau Man; Lee, Seul A.; Naidovski, Nicholas; Liu, Fang; Tay, Alfred Chin Yen; Wang, Liang; Riordan, Stephen; Zhang, Li (Frontiers in Microbiology, 2024)
Campylobacter concisus is an oral bacterium. Recent studies suggest that C. concisus may be involved in human gastric diseases. The mechanisms, however, by which C. concisus causes human gastric diseases have not been investigated.Here we examined the gastric epithelial pathogenicity of C. concisus using a cell culture model. Six C. concisus strains and the human gastric epithelial cell line AGS cells were used. IL-8 produced by AGS cells after incubation with C. concisus was measured using enzyme-linked immunosorbent assay (ELISA), and AGS cell apoptosis was determined by caspase 3/7 activities. The effects of C. concisus on actin arrangement in AGS cells was determined using fluorescence staining. The effects of C. concisus on global gene expression in AGS cells was determined by transcriptomic analysis and real-time quantitative PCR (qRT-PCR). The role of the upregulated CYP1A1 gene in gastric cancer survival was assessed using the Kaplan-Meier method.C. concisus induced production of IL-8 by AGS cells with strain variation. Significantly increased caspase 3/7 activities were observed in AGS cells incubated with C. concisus strains when compared to AGS cells without bacteria. C. concisus induced actin re-arrangement in AGS cells. C. concisus upregulated 30 genes in AGS cells and the upregulation of CYP1A1 gene was confirmed by qRT-PCR. The Kaplan-Meier analysis showed that upregulation of CYP1A1 gene is associated with worse survival in gastric cancer patients.Our findings suggest that C. concisus may play a role in gastric inflammation and the progression of gastric cancer. Further investigation in clinical studies is warranted.